Monetary transmission in money markets: The not-so-elusive missing piece of the puzzle - Zhengyang Chen; Victor J. Valcarcel (Journal of Economic Dynamics and Control, 2021)
We investigate the effects of U.S. monetary policy shocks from alternative policy indicators for a modern sample encompassing 1988–2020. The choice of the Wu and Xia (2016) shadow federal funds rate leads to persistent price puzzles. These puzzles arise despite inclusion of the usual suspect fixes such as commodity prices, federal funds futures and forward rate data. We find they occur at monthly and quarterly frequencies. We consider alternative indicators with the same broad monetary aggregates Keating et al. (2019) employed in their investigation of a historical sample. They provide a consistent resolution of the price puzzle and they do not require the ad hoc inclusion of commodity prices or futures data. This price puzzle correction is not a feature of our time-varying approach as it also obtains from constant parameter econometric estimation. Our analysis suggests monetary policy has transmitted substantial expansionary effects in money markets in the aftermath of the 2007 Financial Crisis and the decade that followed.
Keywords: E3; E4; E5; 330; Price puzzle; Divisia money; Interest rate pass-through; TVP-VAR; TVP-FAVAR; Unexpected monetary policy shocks